The criminals of Lima and their worlds the prison experience, 1850-1935 - Aguirre, Carlos 1958- (Duke University Press, 2005)
Introduction -- Part I. Apprehending the Criminal -- 1. The Emergence of the Criminal Question (1850/1890) -- 2. The Science of the Criminal (1890/1930) -- 3. Policing and the Making of a Criminal Class -- Part II. Prisons and Prison Communities -- 4. Lima's Penal Archipelago -- 5. Faites, Rateros, and Disgraced Gentlemen: Lima's Male Prison Communities -- Part III. The World They Made Together -- 6. Daily Life in Prison; I: The Customary Order -- 7. Daily Life in Prison; II: Prison Subcultures and Living Conditions -- 8. Beyond the Customary Order -- Conclusion